2019
DOI: 10.3390/atoms7010026
|View full text |Cite
|
Sign up to set email alerts
|

On the Time Scales of Optical Variability of AGN and the Shape of Their Optical Emission Line Profiles

Abstract: The mechanism of the optical variability of active galactic nuclei (AGN) is still very puzzling. It is now widely accepted that the optical variability of AGN is stochastic, producing red noise-like light curves. In case they were to be periodic or quasi-periodic, one should expect that the time scales of optical AGN variability should relate to orbiting time scales of regions inside the accretion disks with temperatures mainly emitting the light in this wavelength range. Knowing the reverberation scales and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Still, to tackle the systematic errors related to zero-point calibration issues, we need additional post-processing if the desired level of uncertainty is a few percent. Chilingarian et al (2018) identified a sample of IMBHs (3 × 10 4 < M BH < 2 × 10 5 M ⊙ ) by applying the NBursts full spectral fitting (Chilingarian et al 2007a,b) to SDSS and SDSS/eBOSS optical spectra in the RCSED catalog (Chilingarian et al 2017) with the virial M BH calibration (Greene & Ho 2004;Bon et al 2019). For our analysis we use a part of this list complemented with new sample of "light-weight" SMBHs selected in a similar fashion, for which we found X-Ray counterparts in archival data from XMM-Newton, Chandra, and Swift observatories.…”
Section: Introductionmentioning
confidence: 99%
“…Still, to tackle the systematic errors related to zero-point calibration issues, we need additional post-processing if the desired level of uncertainty is a few percent. Chilingarian et al (2018) identified a sample of IMBHs (3 × 10 4 < M BH < 2 × 10 5 M ⊙ ) by applying the NBursts full spectral fitting (Chilingarian et al 2007a,b) to SDSS and SDSS/eBOSS optical spectra in the RCSED catalog (Chilingarian et al 2017) with the virial M BH calibration (Greene & Ho 2004;Bon et al 2019). For our analysis we use a part of this list complemented with new sample of "light-weight" SMBHs selected in a similar fashion, for which we found X-Ray counterparts in archival data from XMM-Newton, Chandra, and Swift observatories.…”
Section: Introductionmentioning
confidence: 99%
“…This allows one to use optical light curves to search and confirm IMBHs (Martínez-Palomera et al 2020) because M BH limits the AGN luminosity. M BH can be measured from broad optical emission line profiles in AGN spectra (Greene & Ho 2004;Bon et al 2019;Chilingarian et al 2018) Data. Chilingarian et al (2018) defined a sample of IMBHs from the analysis of optical spectra with the NBursts full spectral fitting (Chilingarian et al 2007a,b) in the RCSED catalog (Chilingarian et al 2017), with M BH estimated between 3 * 10 4 M and 2 * 10 5 M .…”
mentioning
confidence: 99%